RIPASA Scores; a Reliable Score for Diagnosis of Acute Appendicitis - Magsi, Abdul Malik; Malik, Mariam; Khan, Muhammad Iqbal (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To establish the diagnostic precision of the RIPASA score for Acute Appendicitis taking histopathology as a gold standard. Methodology: Cross-Sectional Study using non-probability consecutive sampling including 484 patients of both gender with migratory abdominal pain to right iliac fossa < 7 days, Fever ?101°F, and WBC >10000mm3. This study was carried out at General Surgery Department, Jinnah Postgraduate Medical Centre Karachi, from May 2017 to February 2018.Patients with ASA scores III-VI, gangrenous appendicitis, peritonitis, and pregnant women were excluded. RIPASA score was assessed on admission, score summated, and had no effects on management. A score> 7.5 was considered positive for acute appendicitis. The diagnosis was made clinically and with the help of abdominal sonography. Postoperatively specimens were sent for histopathology; results were noted, and diagnostic accuracy was recorded. SPSS version 22 was used to analyze the data. Results: The age range was 20 to 50 years with a mean of 33.892±7.36 years, mean duration of complaint was 3.161±1.16 days, and mean weight was 79.402±8.42 Kg. The majority of patients were males (68.4%). Ripasa score > 7.5 diagnosed 78(16.1%) and 83(17.1%) confirmed by histopathology. Ripasa score > 7.5 had 83.1% sensitivity, 97.8% specificity and diagnostic accuracy 95%, PPV 88.46%, NPV 96.55%, Likelihood positive and negative ratio 37.04 and 0.172 respectively. Ripasa score of 6.5 had a sensitivity of 85.5% and specificity of 94.3%, as shown by the ROC curve and its coordinates. Conclusion: RIPASA is a manageable and comprehensive scoring system with high sensitivity and specificity for diagnosing acute appendicitis. Keywords: Acute appendicitis, RIPASA, Diagnostic accuracy, Right Iliac fossa’s pain, ROC (Receiver Operating Characteristic), Reliable score.